Material Flow Cost Accounting (MFCA) enablers and barriers: the case of a Malaysian small and medium-sized enterprise (SME) - Sulong, Farizah; Sulaiman, Maliah; Mohd Alwi, Norhayati (Elsevier Inc., 2015)
The introduction of Material Flow Cost Accounting (MFCA) to five companies under the Malaysia Productivity Corporation (MPC) project has shown that these companies have indeed achieved simultaneous benefits of economic gains and environmental sustainability. This paper highlights the experience of one of the companies, emphasising how one can leverage enablers and also overcome barriers to implementing MFCA in a small and medium-sized enterprise (SME) in Malaysia. Driven by the diffusion of innovation (DOI) theory, the case company found most of its enablers within MFCA's own attributes. Additionally other factors such as the team composition, interpersonal communication, and efforts of the change agents were instrumental in the success of the MFCA implementation. However, the company was also constrained by its suppliers. More importantly, it is envisaged that a potential hurdle for MFCA advancement is when performance management issues are not addressed by higher management. Drawing upon the company's experience and the theoretical literature, other barriers that may also be encountered by SMEs in Malaysia are also discussed. These include for example, overcoming the traditionalist view held by most SMEs, persevering the implementation processes on their own without the direct assistance from MPC and several others.